Combustion characteristics of microalgae-based dioctyl phthalate biofuel during ambient, preheated and hot engine operation. (1st January 2023) - Lodi, Faisal; Zare, Ali; Arora, Priyanka; Stevanovic, Svetlana; Ristovski, Zoran; Brown, Richard J; Bodisco, Timothy
Highlights: Combustion analysis was conducted using Di-octyl Phthalate (DOP) blended with diesel. During ambient start, DOP blends recorded higher pressure rise rate and peak AHRR. Ignition delay increased and combustion duration decreased as DOP percentage increased. Combustion parameters were influenced by fuel-bound oxygen and in-cylinder temperature. In-cylinder temperature was higher using blended fuels during ambient operation. Abstract: Presented in this article is a comprehensive analysis of combustion behaviour using Di-octyl Phthalate (DOP) – an oxygenated third-generation biofuel, blended with ultra-low sulphur diesel (D100) in proportions of 10 % (DOP10D90) and 20 % (DOP20D80) ( %v/v ). The experiments were conducted on a heavy-duty diesel engine during ambient, preheated and hot engine operation. A cold-engine custom-designed drive cycle, with frequent engine stop/start was used. D100 was found to warm up faster by 7 % during the first 120 s of ambient operation, compared to DOP blended fuels. The maximum rate of pressure rise was 18 % and 14 % higher using DOP10D90 and DOP20D80, respectively, compared to D100. Peak apparent heat release rates (AHRR) were 11 % and 7 % higher using DOP10D90 and DOP20D80 fuels, respectively, compared to D100 during the first 120 s of ambient operation. Oxygen bound to the fuel molecule caused an increase in the maximum rate of pressure rise and an increase in the peak AHRR during ambient operation. As the DOP quantity increased in the fuel blend, the ignition delay increased, while the combustion duration decreased. Neither of these parameters was affected by engine warm-up. The shortest combustion duration was observed using DOP20D80, leading to a faster burn rate during the premixed combustion stage during ambient start, compared to DOP10D90 and D100.